WOMEN’S COSTUMES OF XINJIANG, GUANGSI AND NINGSIA IN CONTEMPORARY EASEAL PAINTING OF CHINA - Чонг, Ван (Art and Design, 2023)
The purpose of this article is to study the stylistic, compositional and coloristic solutions of the representation of the traditional women’s costume of the regions of Xinjiang, Guangxi and Ningxia. in modern Chinese genre painting. The research methodology is based on the use of both general scientific methods of analysis and special art-scientific methods, namely: methods of formal-stylistic and compositional-coloristic analysis. The article analyzes the traditional elements of the women’s costume of Xinjiang, Guangxi and Ningxia, which are still used in the everyday life of modern China. Both sociocultural and purely artistic factors that influenced the use of traditional women’s costumes in the specified areas of the country are characterized. It has been proven that at the end of the 20th and the beginning of the 21st centuries, adapted versions of the traditional women’s costumes of Xinjiang, Guangxi and Ningxia are represented in Chinese easel painting. Thoughtful techniques, compositional and coloristic solutions of easel paintings by modern Chinese artists, in which the traditional women’s costumes of Xinjiang, Guangxi and Ningxia are represented. It was found that modern Chinese easel artists actively represent the traditional women’s costume in different styles, in particular, in a realistic style. It has been proven that the specific cultural features of the women’s costume of each of these regions are represented in the work of such easel artists as Abdul Kerim Nasir al-Din, Liu Bingjiang, Jin Shanyi, Huang Jin, Cun Ruixuan, Shen Mingcun, Xue Boyuan, Cai Liang and Chen Baoyi. its cut, texture, color palette, decorations and embroidery. The paintings of modern domestic easel painters, showing traditional women’s costumes, reflect through them the social roles played by the women of these regions, their traditional duties and their influence on the cultural norms of their ethnic groups. The scientific novelty of the obtained results lies in the fact that the article systematically examines the variants of the representation of the female costume of Xinjiang, Guangxi and Ningxia in the easel painting of modern China. The practical significance of the obtained results lies in the possibility of their application for professional art education both in Ukraine and in China. The study opens the perspective of studying different versions of the representation of women’s costumes of different regions of China in modern easel painting.